2020
DOI: 10.1055/s-0040-1713174
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Outcomes of Reconstructive Breast Surgery: An Analysis of 51,362 Patients from the ACS-NSQIP

Abstract: Background In various surgical specialties, racial disparities in postoperative complications are widely reported. It is assumed that the effect of race can also be found in plastic surgical outcomes, although this remains largely undefined in literature. This study aims to provide data on the impact of race on outcomes of reconstructive breast surgery. Methods Data were collected using the NSQIP (National Surgical Quality Improvement Program) database (2008–2016). Outcomes of the reconstructive brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
14
1
Order By: Relevance
“…Our results differ from other published reports looking at overall racial disparities in chest surgeries, 32 which did not find racial differences in the complications of breast procedures performed in the NSQIP database. This difference is possibly due to the fact that previous research examined only all-cause complications rather than individual complications in the NSQIP.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differ from other published reports looking at overall racial disparities in chest surgeries, 32 which did not find racial differences in the complications of breast procedures performed in the NSQIP database. This difference is possibly due to the fact that previous research examined only all-cause complications rather than individual complications in the NSQIP.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, both of our study cohorts were relatively healthy, with >90% of the overall sample classified as ASA Class 1 or 2. In contrast, previous research on breast reconstruction has indicated fairly high rates of comorbidities and overall poorer health 32,33…”
Section: Discussionmentioning
confidence: 88%
“…In addition to challenges with access to breast reconstruction, AA patients have been shown to have increased comorbidities, equivocal clinical outcomes, and decreased preoperative and postoperative satisfaction compared with white patients. 8,15,25,[33][34][35][36] Numerous studies have demonstrated higher levels of hypertension, diabetes, increased BMI, and smoking among AA patients compared with white patients. 3,8,34,35,37 These, in addition to other differences in preoperative risk factors, such as heart disease, pulmonary disease, and chronic kidney disease, have further informed our understanding of the impact of socioeconomic factors on general health, wellness, and adequate provision of care.…”
Section: Comorbidities Outcomes and Satisfactionmentioning
confidence: 99%
“…8,15,25,[33][34][35][36] Numerous studies have demonstrated higher levels of hypertension, diabetes, increased BMI, and smoking among AA patients compared with white patients. 3,8,34,35,37 These, in addition to other differences in preoperative risk factors, such as heart disease, pulmonary disease, and chronic kidney disease, have further informed our understanding of the impact of socioeconomic factors on general health, wellness, and adequate provision of care. 18,20,[38][39][40][41] Despite increased comorbidities and risk factors, studies comparing postoperative complications after breast reconstructive between racial and ethnic groups are inconclusive.…”
Section: Comorbidities Outcomes and Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation